Drug delivery systems and novel formulations to improve treatment of rare corneal disease. Issue 8 (August 2019) - Jimenez, Jorge; Sakthivel, Meera; Nischal, Kanwal K.; Fedorchak, Morgan V.
Highlights: Rare corneal disease research is a growing field with potential advantages for drug reformulation. Treatment of rare corneal diseases could be improved with techniques used in common ocular diseases. Current investigations of novel formulations for rare corneal diseases show tremendous promise. Abstract : As the field of ocular drug delivery grows so does the potential for novel drug discovery or reformulation in lesser-known diseases of the eye. In particular, rare corneal diseases are an interesting area of research because drug delivery is limited to the outermost tissue of the eye. This review will highlight the opportunities and challenges of drug reformulation and alternative treatment approaches for rare corneal diseases. The barriers to effective drug delivery and proposed solutions in development will be discussed along with an overview of corneal rare disease resources, their current treatments and ophthalmic drug delivery systems that could benefit such cases. The regulatory considerations for effective translation of orphan-designated products will also be discussed. Teaser: Overview of current and future opportunities for treatment of rare corneal diseases and application of ophthalmic drug delivery systems.